UNJUK KERJA PROSES PIROLISIS KATALITIK LIMBAH BAN BEKAS MENJADI BAHAN BAKAR CAIR DITINJAU DARI JUMLAH KATALIS, VARIASI TEMPERATUR, DAN WAKTU OPERASI - Effendy, Sahrul; Rusnadi, Irawan; ., Fatria; Amin, Jaksen M.; Aina, Nur; Rossa, Briliantina; Waltin, Muhammad (Politeknik Negeri Sriwijaya, 2021)
Indonesia's domestic rubber consumption is largely absorbed by the manufacturing industry, especially the automotive industry. The more production of vehicle, the more people will produce tires. As a result, the waste of tires in the environment is increasing. One of the alternatives to reduce the amount of tires waste is produce it become liquid fuel by catalytic pyrolysis method. The purpose of this research is to analyze percent yield liquid product and to obtain characteristics of liquid fuel observed by the number of catalyst, variation of temperature, and operation time. The result shown that the optimum temperature is 400oC using 10% NZ catalyst with product yield of 13.0284%. The optimum NZ catalyst is 2% at 300oC with product yield of 5.7946%. Also the optimum time operation is 180 minutes using 10% NZ catalyst with product yield of 9.7965%. The liquid fuel oil spesifications obtain diesel oil by testing density, viscosity, and flash point. The liquid fuel also analyzed by the GC-MS method, and it can be concluded that the liquid fuel of tires waste is mixture of gasoline (C8-C12) and diesel (C13-C20).